Behavior of leadless AV synchronous pacing during atrial arrhythmias and stability of the atrial signals over time—Results of the MARVEL Evolve subanalysis. Issue 3 (12th February 2019) - Garweg, Christophe; Splett, Vincent; Sheldon, Todd J.; Chinitz, Larry; Ritter, Philippe; Steinwender, Clemens; Lemme, Francesca; Willems, Rik
Abstract: Introduction: The MARVEL study demonstrated at a single time point that accelerometer (ACC)‐based atrial sensing improves atrioventricular (AV) synchrony (AVS) in patients with AV block and a Micra pacemaker (Medtronic, Minneapolis, MN, USA). The purpose of the MARVEL Evolve substudy was to assess the performance over time. Methods: This prospective single‐center study compared AVS and ACC signals at two visits ≥6 months apart. Custom software was temporarily downloaded into the Micra at each visit and AVS was measured during 30 min at rest. Results: Nine patients from the MARVEL study were enrolled. The mean (±standard deviation) age was 82.3 ± 6.0 years old, 67% were male, and a Micra was implanted for 6.0 ± 6.4 months. High‐degree AV block was present in four patients, whereas five with predominantly intrinsic conduction required intermittent pacing for bradycardia. The mean interval between visits was 7.1 ± 0.6 months. Seven patients had normal sinus node function at both visits and were included in a paired analysis. Both ACC signal amplitude (visit 2‐visit 1 = 1.4 mG; 95% confidence interval [CI] [−25.8 to 28.4 mG]; P  = 0.933) and AVS (visit 1: 90.8%, 95% CI [72.4, 97.4] and visit 2: 91.4%, 95% CI [63.8, 98.5]; P  = 0.740) remained stable. Three patients had spontaneous atrial tachycardia. During atrial fibrillation, no atrial contraction was detected or tracked. During atrial flutter, intermittent tracking resulted in a ventricular rate of 60 ± 8 beats per minute (bpm); there was no ventricular pacing >100 bpm. Conclusion: ACC signals amplitude and performance of AVS pacing were stable over time. During atrial arrhythmias, the AV synchronous pacing mode behaved safely.